Regulatory and Policy Barriers to Marine Renewable Energy in Indonesia (Collaborate Engineering Daily Book Series, 2025)
Indonesia possesses vast potential for marine renewable energy (MRE), including tidal, ocean current, and ocean thermal energy (OTEC). However, its utilization remains significantly below the national energy mix targets. This perspective article examines the gap between Indonesia’s energy transition ambitions and the existing regulatory realities. Through a critical review of current policies, we identify three major barriers: (1) overlapping authority among institutions, (2) the absence of a dedicated fiscal incentive framework for marine technologies, and (3) the lack of a comprehensive and integrated national roadmap within the National Energy General Plan (RUEN). We argue that without cross-sectoral regulatory alignment and legal certainty for investors, the potential of MRE will remain largely untapped. This article highlights the importance of establishing a “one-stop” policy framework and developing a technology roadmap that reflects Indonesia’s archipelagic characteristics. In conclusion, strengthening regulatory frameworks is not merely an administrative step, but a fundamental prerequisite for positioning marine energy as a pillar of Indonesia’s future energy sovereignty.
Keywords: Marine Renewable Energy; Energy Policy; National Roadmap; Regulatory Barriers; Energy Transition